Drug wastage and costs to the healthcare system in the care of patients with non-small cell lung cancer in the United States. (3rd August 2018) - Hess, Lisa M.; Cui, Zhanglin Lin; Li, Xiaohong Ivy; Oton, Ana B.; Shortenhaus, Scott; Watson, Ian A.
Abstract: Background: Lung cancer is one of the most prevalent cancers in the US. This study was designed to evaluate the actual drug wastage and cost to the healthcare system using patient-level retrospective observational electronic medical record (EMR) data from a cohort of lung cancer patients in the US. Methods: Data from the Flatiron Health advanced non-small cell lung cancer (NSCLC) cohort was used for this study. Drug administered amount (in mg) was used to determine an optimal set of available vial sizes to minimize waste. Drug wastage was defined as the difference between the drug amount in the optimal set of vials and the administered amount. Wholesale acquisition costs were used to value the cost of drugs, with and without vial sharing assumptions. The amount and cost of waste were quantified over the 2-year study period (January 2015–December 2016). Results: There were 8, 467 eligible patients included in this study, providing data from 103, 826 unique drug administrations across multiple lines of therapy. Overall wastage was 4.37% of the total medication used to care for patients. While costs per administration were low, the total cost of wastage for the study population represented 16, 630, 112 across the 2-year study period. Assuming that vial sharing occurred at the site level slightly reduced waste to 3.74% (reducing costs to 15, 953, 212 over 2 years). Conclusions: Drug wastage is an important concern and has implications on healthcare costs in NSCLC. Evaluation of these real-world data suggest that pharmacists and physicians are able to reduce drug wastage by optimizing vial combinations and sharing vials among patients. Even small amounts of reduction in wastage could be useful in reducing healthcare costs in the US; however, caution is needed with drug rounding efforts to ensure patients do not receive a sub-optimal dose of medication.